Non-phytotoxic concentration of nemarioc-AL and nemafric-BL phytonematides on green bean cultivar "Tahoe" - Chokoe, Francinah Mologadi (My University, 2017)
Refer to document
Thesis ( M.Sc.(Horticulture)) -- University of Limpopo, 2017.
Keywords: Nemarioc-AL phytonematicides; Nemafric-AL phytonematicides; Green beans; Agricultural productivity -- South Africa; Beans -- Field experiments